Environmental impact of amino acids on selenate-bearing hydrocalumite: Experimental and DFT studies. (1st November 2021) - Wang, Mengmeng; Akamatsu, Hirofumi; Dabo, Ismaila; Sasaki, Keiko
Abstract: Selenium (Se) radioactive wastes can be disposed through stabilization/solidification (S/S) based on the cementitious matrix on hydration products, where hydrocalumite (Ca2 Al-LDH) is expected to play an important role in the retention of SeO4 2− . Natural organic matters (NOMs) are known to be a risk to affect the transportation and mobility of undesirable chemical species in the pedosphere which receives the low level radioactive wastes (LLW). In the present work, five amino acids were selected as the simplified models of NOMs in the pedosphere to explore their effects on the stability of Ca2 Al-LDH after immobilized SeO4 2− under alkaline conditions. As the loading amount of amino acids on Ca2 Al-LDH increasing, release of SeO4 2− was enhanced in HGly, H2 Asp, and H2 Cys series, while no enhancement was observed in HPhe and HTrp series. Density functional theory (DFT) calculation predicted ion-exchange of amino acids and CO3 2− with SeO4 2− in a unit cell of LDH model. The intercalation of Asp 2− and CO3 2− caused 003 peaks in XRD sharper and d 003 decreased from 8.15 Å to 7.70 Å which is assigned to Ca2 Al-LDH(Asp, CO3 ). In H2 Cys series, the 003 peaks were kept broad and SeO4 2− was still relatively maintained in LDH which was caused by the lower amounts of intercalated CO3 2− in the presence of H2 Cys. Amino acids in the interlayer of Ca2 Al-LDH have several possible configurations, where the most stable one is prone to be in a horizontal direction through hydrogen bonds and Ca–O chemical bonds. This provides an insight on the stability of selenate immobilized in hydrocalumite, which can be produced in cement disposing in the pedosphere for a long term of burying. Not only carbonate but also small molecular organic matters like amino acids possibly give environmental impact on the mobility of low level anionic radionuclides in LDH. Graphical abstract: Image 1 Highlights: Effects of amino acids on the mobility of SeO4 2− bearing Ca2 Al-LDH were studied. H2 Asp, H2 Cys and HGly promoted releasing of SeO4 2− from Ca2 Al-LDH. DFT simulation predicted the intercalation of Asp 2− and Cys 2− in Ca2 Al-LDH. CO3 2− can co-exist with Asp 2− stably in Ca2 Al-LDH to enhance SeO4 2− release.